MO307POLYCLONAL FREE LIGHT CHAINS AS A PREDICTOR OF CKD PROGRESSION IN NONPROLIFERATIVE GLOMERULOPATHIES. (29th May 2021) - Churko, Anna; Khrabrova, Maria; Smirnov, Alexei; Sipovski, Vassili; Panina, Iraida
Abstract: Background and Aims: The mechanism of the epithelial-mesenchymal transition of kidney tubular cells leading to kidney fibrosis formation and CKD progression is well described for monoclonal free light chains (FLC) in patients with monoclonal gammopathies. As far as the interaction of FLC with megalin/cubulin receptors on proximal tubular epithelial cells is considered to be universal we hypothesize that polyclonal free light chains (pFLC) could have the same effect on tubulointerstitial compartment in patients with primary glomerulopathies. This retrospective study was performed to reveal the association of serum pFLC kappa (pFLC-κ) and lambda (pFLC-λ) assessed by Freelite® with clinical and morphological parameters and CKD progression in patients with nonproliferative glomerulopathies. Method: 36 patients with morphologically proven diagnosis of nonproliferative glomerulopathies (minimal changed disease (n=11), membranous nephropathy (n=11) and focal segmental glomerulosclerosis (n=14)) were included. Serum levels of pFLC-κ and pFLC-λ were assessed by Freelite® (normal ranges: κ=3.3-19.4 mg/l; λ=5.7-26.3 mg/l; κ/λ ratio=0.26-1.65) at the time of kidney biopsy (KBx) in all cases. Patients with abnormal κ/λ-ratio due to monoclonal gammapathies were excluded. Apart demographical parameters, serum creatinine, estimated GFR (eGFR) by CKD-EPI, serum albumin and 24-hour proteinuria were measured. Morphological findings defined by light microscopy were measured semiquantitatively according to currently accepted criteria (0 - <10%, 1 - 10-25%, 2 – 26-50%, 3 - >50% of tissue involved). Data are presented as median and interquartile range (M (25%; 75%)) and mean and the standard error of mean (m±SEM) for semiquantitative parameters or %. Correlation between parameters was assessed by Spearman's coefficient. Progression of CKD was determined as decline of eGFR >15% from the initial level at the end of follow-up. Cox proportional hazards regression was used to estimate the association of pFLC and other parameters with CKD progression. Differences were considered statistically significant at p <0.05. Median follow-up was 11 (1; 53) months. Results: Demographic and clinical parameters at the time of KBx are shown in the Figure 1 . Clinical and morphological parameters as well as correlation analysis data are presented in the Figure 2 . Univariant Cox regression shows that pFLC-λ >N ( Exp(β)=5.120 ; 95% CI: 1.011-25.924, p<0.05 ), both pFLC-κ and pFLC-λ >N ( Exp(β)=6.646 ; 95% CI: 1.327-33.287, p=0.02 ), κ/λ ratio ( Exp(β)=4.656 ; 95% CI: 1.411-15.362, p=0.01 ), as well as percent of sclerotic glomeruli ( Exp(β)=1.039 ; 95% CI: 1.006-1.073, p=0.01 ), glomerular basement membrane segmental thickening ( Exp(β)=3.129 ; 95% CI: 1.213-8.071, p<0.01 ), mesangial proliferation ( Exp(β)=5.177 ; 95% CI: 1.146- 23.396, p=0.03 ), interstitial cell infiltration ( Exp(β)=3.777 ; 95% CI: 1.258-11.340, p=0.02 ) and peritubular capillaritis ( Exp(β)=5.177 ; 95% CI: 1.146- 23.396, p=0.03 ) were associated with CKD progression. Conclusion: In nonproliferative glomerulopathies increased level of pFLC, either kappa or lambda, is associated with glomerular lesion, interstitial inflammation, tubular atrophy and interstitial fibrosis. Moreover, elevated levels of pFLC could be proposed as a predictor of CKD progression in studied patient cohort. The mechanisms of kidney injury by pFLC requires further investigation.